The Effect of Marketing Public Relations on Brand Image - Inggrid Sinaga (Politeknik Negeri Batam, 2014)
The purpose of this research was 1 ) to identify the factors of the Marketing and Public Relations. 2) Explain the influence factors of Marketing and Public Relations of the brand image. Research by using factor analysis known that there are four new factors: publications, news, sponsorship and media identity. The results of multiple linear regression analysis showed that factors publications, news factors, factors sponsorship, media and identity factors jointly significant effect on brand image variables. From the results of the partial regression showed Publication factor is the dominant factor influence the brand image